Guidelines in CHARGE syndrome and the missing link: Cranial imaging. Issue 4 (23rd November 2017) - de Geus, Christa M.; Free, Rolien H.; Verbist, Berit M.; Sival, Deborah A.; Blake, Kim D.; Meiners, Linda C.; van Ravenswaaij‐Arts, Conny M. A.
Abstract : "CHARGE syndrome" is a complex syndrome with high and extremely variable comorbidity. As a result, clinicians may struggle to provide accurate and comprehensive care, and this has led to the publication of several clinical surveillance guidelines and recommendations for CHARGE syndrome, based on both single case observations and cohort studies. Here we perform a structured literature review to examine all the existing advice. Our findings provide additional support for the validity of the recently published Trider checklist. We also identified a gap in literature when reviewing all guidelines and recommendations, and we propose a guideline for neuroradiological evaluation of patients with CHARGE syndrome. This is of importance, as patients with CHARGE are at risk for peri‐anesthetic complications, making recurrent imaging procedures under anesthesia a particular risk in clinical practice. However, comprehensive cranial imaging is also of tremendous value for timely diagnosis, proper treatment of symptoms and for further research into CHARGE syndrome. We hope the guideline for neuroradiological evaluation will help clinicians provide efficient and comprehensive care for individuals with CHARGE syndrome.